Impact of systemic sclerosis on electromechanical characteristics of the heart - TİGEN, MUSTAFA KÜRŞAT (SPRINGER, 2010)
Primary myocardial involvement is common in systemic sclerosis (SSc). We evaluated the atrial and ventricular electromechanical characteristics by using tissue Doppler echocardiography in SSc patients with subclinical cardiac involvement. Twenty-seven consecutive patients (24 women; mean age +/- SD 49.9 +/- 11.3 years) presenting with SSc without pulmonary arterial hypertension or symptomatic heart failure were prospectively studied. Electrocardiographic P-wave dispersion (Pd), corrected QT dispersion (QTcd), interatrial, intra-atrial, interventricular, and intraventricular electromechanical delays were analyzed by tissue Doppler echocardiography, and brain natriuretic peptide levels were measured. Results were compared with 17 healthy controls. There was no difference in conventional and tissue Doppler parameters between the two groups. However, patients with SSc had higher mean Pd (mean [+/- SD] 46.8 +/- 15 and 36 +/- 8 ms, respectively, P = 0.004) and mean interatrial electromechanical delay time (DT) (mean [+/- SD] 32.2 +/- 9.2 and 24.7 +/- 9.7 ms, respectively, P = 0.01), mean electromechanical delay time for all segments (Mean Ts) (mean [+/- SD] 148.8 +/- 18.8 and 129.3 +/- 13.4 ms, respectively, P < 0.001), and intraventricular DT (mean [+/- SD] 27.6 +/- 12.5 and 16.2 +/- 7.2 ms, respectively, P < 0.001). Intraventricular DT was the only parameter that correlated significantly with the Mean Ts. Brain natriuretic peptide levels were within normal limits in both groups; however, they were higher in patients with SSc than in controls (mean [+/- SD] 37.5 +/- 28.5 and 23.1 +/- 16.0 pg/ml, respectively, P = 0.03). The evaluation of atrial and ventricular electromechanical parameters by using tissue Doppler echocardiography seems to be useful for detection of subclinical cardiac involvement in SSc patients with normal conventional echocardiographic findings.
Keywords: Connective tissue disorder; Electromechanical delay; Conduction abnormality; TISSUE-DOPPLER-ECHOCARDIOGRAPHY; CARDIAC INVOLVEMENT; MYOCARDIAL FIBROSIS; CONDUCTION SYSTEM; QT DISPERSION; SCLERODERMA; ARRHYTHMIAS; ABNORMALITIES; DYSFUNCTION; DISEASE